>>605 まず π^2/6 = 2 - 1/(1^2*1*3) - 1/(2^2*3*5) - 1/(3^2*5*7) - … を導く。
1/(1^2*1*3) + 1/(2^2*3*5) + 1/(3^2*5*7) + …
=(1/1^2)(4/(1*3)-1) + (1/2^2)(16/(3*5)-1) + (1/3^2)(36/(5*7)-1) + …
=(4/(1*3)-1/1^2) + (4/(3*5)-1/2^2) + (4/(5*7)-1/3^2) + …
=(2/1-2/3-1/1^2) + (2/3-2/5-1/2^2) + (2/5-2/7-1/3^2) + …
=2 - π^2/6
従って
π^2 = 6{ 2 - 1/(1^2*1*3) - 1/(2^2*3*5) - 1/(3^2*5*7) - … }
= 12 - 2 - 1/10 - 2/105 - 1/168 - …
両辺の2乗は
(√2+√3)^2 = 5+2√6 = 10-(5-2√6) = 10-(√25-√24)
π^2 = 10 - (1/10+2/105+1/168+…) = 10-(5/42+1/168+…)
10から引かれる値の大小関係は
√25-√24 = 1/(√25+√24) < 1/(5+√16) = 5/45 < 5/42 < 5/42+1/168+…
従って (√2+√3)^2 > π^2 つまり √2+√3 > π